2014
DOI: 10.1016/j.jval.2014.08.1272
|View full text |Cite
|
Sign up to set email alerts
|

Which Adverse Effects Influence the Dropout Rate in Selective Serotonin Reuptake Inhibitor (Ssri) Treatment?

Abstract: in terms of longer length of stay, more readmissions and higher consumption of drugs. The average quality of the studies was moderate. Further research is needed to establish the degree of burden of agitation and containment borne by hospitals and the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Another possibility for this high dropout rate could be the potential side effects that arose from the intervention. This has been already shown extensively in the literature, in which increased dropout rate in drug trials is significantly associated with adverse effect severity [19,20]. This could certainly be the case in this study, as participants with SCI submitted to verum stimulation reported significant more skin redness, sleepiness, scalp pain, scalp burning sensation, and tingling as compared to those receiving the placebo.…”
Section: Discussionsupporting
confidence: 72%
“…Another possibility for this high dropout rate could be the potential side effects that arose from the intervention. This has been already shown extensively in the literature, in which increased dropout rate in drug trials is significantly associated with adverse effect severity [19,20]. This could certainly be the case in this study, as participants with SCI submitted to verum stimulation reported significant more skin redness, sleepiness, scalp pain, scalp burning sensation, and tingling as compared to those receiving the placebo.…”
Section: Discussionsupporting
confidence: 72%
“…Selective Serotonin Receptor Inhibitors (SSRIs) are the most commonly prescribed antidepressants with a prevalence of use in adults of 4%‐8.5% depending on geographical location . Although treatment with SSRIs is generally well tolerated, a recent meta‐analysis found that treatment with SSRIs was associated with a 1.55‐fold increase in the risk of developing upper gastrointestinal bleeding compared to patients who had not taken SSRIs . The risk of developing upper gastrointestinal bleeding was particularly increased in patients taking concurrent nonsteroidal anti‐inflammatory drugs (NSAIDs; odds ratio [OR]: 3.72), or concurrent antiplatelet drugs (OR: 2.48) .…”
Section: Introductionmentioning
confidence: 99%
“…29,30,35 . In this way, we can see that since these drugs act on the central nervous system, they produce lots of effects on the organism, and therefore, they are among the treatments that generate more ADR in our study.…”
Section: Discussionmentioning
confidence: 99%